Major and trace elements of Aegean Arc tephras - Kutterolf, Steffen; Freundt, Armin; Hansteen, Thor H; Dettbarn, Rebecca; Hampel, Fabian; Sievers, Carina; Wittig, Cathrin; Allen, Sharon R; Druitt, Timothy H; McPhie, Jocelyn; Nomikou, Paraskevi; Pank, Katharina; et al. (PANGAEA, 2021)
Here the data are archived that belong to the paper: The medial offshore record of explosive volcanism along the central to eastern Aegean Volcanic Arc, part 1: Tephrostratigraphic correlations submitted for publication at G-Cubed. In table 2a average major and trace element compositions are given for analyses correlative land tephras. In Table 2b the entire set of individual glass shard measurements are given. In Table 3a the average major and trace element compositions of marine tephras found in the cores of Table 1 are given. Table 4 represents the microprobe reference measurements on Lipari and VGA99 with respective reference values as well as List standard N612 and BCR2 for trace element measurements, Table 5 show the results of the principal component analyses and the extracted eigenvectors of 88 parameter reduced to 10 principal components.
Keywords: Major and Trace elements Aegean land tephra; reference glass measurements